Broiler farming and antibiotic use through an agency theory lens. A case study from West Bengal, India. - Mathew Hennessey; Indranil Samanta; Guillaume Fournié; Matthew Quaife; Meenakshi Gautham; Haidaruliman Paleja; Kumaravel Papaiyan; Ripan Biswas; Pablo Alarcon (PLoS ONE)
Chicken meat (broiler) production is a rapidly growing livestock sector in India, and one dominated by contract farming. Studies have reported high levels of antibiotic use in Indian broiler farms which is concerning given this is one of the driving forces for the development of antibiotic resistance. This study used the economic lens of agency theory to examine strategic decisions which occur during contract broiler production and their potential impact on antibiotic use, using West Bengal as a case study. Agency theory focuses on the informational asymmetry and opportunism between service providers and seekers and the subsequent agency cost needed to avoid aberrant outcomes. Interviews were conducted with key informants (n = 6) and stakeholders (n = 20) associated with broiler production, and broiler farmers (17 contract and four non-contract), using online and face-to-face interviews. Data were analysed descriptively using manifest content analysis and interpretatively using reflexive thematic analysis. Contract farming in West Bengal exists within a series of inter-dependent relationships, many of which contain information asymmetry and can be subject to opportunism. Positioning contract companies as principals seeking labour from agents, we see how out-sourcing of production to distal farms led to antibiotics being used as a risk mitigation strategy. This was further compounded by concerns about the Mycoplasma status of breeding stock, and a perception that broiler day old chicks were infected, resulting in use of antibiotics belonging to classes deemed critically important for human health. While antibiotic use decisions were predominately made by contract companies, they were dependent on the decisions farmers and breeding companies made concerning biosecurity and production practices. In turn, farmers' decisions were shaped by factors such as access to financial and social capital. Thus, efforts to reduce antibiotic use in West Bengal's broilers must not just focus on changing the prescribing behavior of individuals but more broadly consider the environment within which contracting exists.